Sistemi di controllo formali nelle pmi familiari: una presenza possibile? - Cattaneo, Cristiana; Bassani, Gaia (Piccola Impresa / Small Business, 2015)
Formal management control systems (MCSs) in family business is an under-studied topic. According to the family context, studies usually refer to informal MCSs and the introduction of formal systems coincide to peculiar situations, such as professionalization or succession. The purpose of this paper is to capture the multitude of determinants enabling the presence of these systems. A survey addressed to Italian construction SMEs highlights some determinants. The process of growth, the macro-economic context of crisis, the lack of a key actor for management and control and the lack of shared values into the management group favour the introduction of formal MCSs. The effects of other variables are not confirmed.